EriofiÃdeos (ACARINA: ERIOPHYIDAE) PREJUDICIAIS Ã€ BATATA-DOCE - Alves, SÃ©rgio Batista; Calafiori, Maria Helena; Paschoal, Adilson Dias (REVISTA DE AGRICULTURA, 2016)
EriofiÃdeos (ACARINA: ERIOPHYIDAE) PREJUDICIAIS Ã€ BATATA-DOCE